(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The argument is that “civilization” is the key term to denote groups and peoples who share a large and common geographic locus, values and social institutions, and that “culture” refers to a particular set of values or beliefs within the larger historico-cultural entity that is a civilization. If we treat “civilization” as the largest and highest socio-historical unit and “culture” as something smaller, lower, and subsumed under “civilization,” we will better understand the ubiquitous phenomenon of cultural appropriation and civilizational hybridization. To further elucidate how these two terms should be understood and to disentangle them from each other, the essay provides an historical account of the context in which each term arose.The associated culture, sometimes referred to as Vedic civilization, was probably centred early on in the northern and northwestern parts of the Indian subcontinent, but has now spread and constitutes the basis of contemporary Indian culture. After the end of the Vedic period, the Mahajanapadas period in turn gave way to the Maurya Empire (from ca. 320 BC), the golden age of classical Sanskrit literature.